Understanding Ocean Literacy and Nautical Love Among Students at Public Senior High School in Subang Regency - Prasetia, Muhamad Faiz; Maryani, Enok; Ruhimat, Mamat (Universitas Pendidikan Indonesia, 2024)
This study discussed the level of understanding of ocean literacy which intended to identify the level of ocean literacy as an effort to foster nautical love in maintaining coastal and ocean preservation in Subang region. The research method used was descriptive with a simple regression test. The results of this study showed that the ocean literacy variable (66%) was in the high category and the nautical love variable was in the medium category (60%). In testing all variables using the T-test, the F test showed significant results, as well as the results of the simple linear regression test indicated that each variable largely influenced the other, with knowledge value (0.115), attitude value (0.468), and behavior value (0.144). The findings of this study revealed that most students have a good level of ocean literacy as well as in the aspect of knowledge and behavior in cultivating a sense of nautical love.